2004
DOI: 10.1007/s10151-004-0139-4
|View full text |Cite
|
Sign up to set email alerts
|

Are there any differences in colorectal cancer between young and elderly patients?

Abstract: Except for a higher rate of undifferentiated adenocarcinoma in young patients, there were no particular differences in the compared factors between the two age groups. The mortality rates do not indicate a less favourable prognosis for the young.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
8
2
3

Year Published

2006
2006
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 4 publications
(3 reference statements)
2
8
2
3
Order By: Relevance
“…26,27 Our study showed a progressive increase in all cases of moderately differentiated lesions over time with a trend toward more differentiated lesions in the distal colon; a finding that has been reported in other studies 28 in which improved grade has been accompanied by a steady decline in mucinous lesions and an increased amount of peritumoral desmoplastic response. This has been accompanied in our study by a nonsignificant reduction in mucinous tumors, a slight but nonsignificant increase in lymphovascular infiltration, and no effect on neural invasion.…”
Section: Discussionsupporting
confidence: 66%
“…26,27 Our study showed a progressive increase in all cases of moderately differentiated lesions over time with a trend toward more differentiated lesions in the distal colon; a finding that has been reported in other studies 28 in which improved grade has been accompanied by a steady decline in mucinous lesions and an increased amount of peritumoral desmoplastic response. This has been accompanied in our study by a nonsignificant reduction in mucinous tumors, a slight but nonsignificant increase in lymphovascular infiltration, and no effect on neural invasion.…”
Section: Discussionsupporting
confidence: 66%
“…Furthermore, a larger part of the patients diagnosed before age 50 years had more advanced disease stage compared to the older age groups. This may reflect that CRC is unexpected in young adults and symptoms are neglected both by the patient and the physician [52]. Reports of young colorectal cancer patients differs with regards to aggressiveness of the disease, and hence outcome [3], [52], [53].…”
Section: Discussionmentioning
confidence: 99%
“…Análise da literatura, quanto à localização dos tumores comparando doentes acima e abaixo de 40 anos, não mostrou diferença, 25,[32][33][34] corroborando com nossa experiência, embora haja relato de que a localização retal é mais comum entre os mais idosos. 27 Revisão da literatura mostrou que o CCR na população mais jovem é mais agressivo, é diagnosticado nos estádios mais avançados [27][28][29] e tem achados histopatológicos mais indiferenciados.…”
Section: Discussionunclassified
“…As taxas de mortalidade não revelaram prognóstico menos favorável para os mais jovens, a exemplo do citado por outros. 32 A literatura mostrou que os tumores está-dio III, na classificação TNM, foram mais comuns nos doentes mais jovens e as lesões estádio II foram mais frequentes nos acima dos 45 anos. 29 Em nossos casos, observamos que o estádio II foi mais comum no grupo dos mais jovens e o IV entre os mais velhos, entretanto sem diferença estatística.…”
Section: Discussionunclassified